2007
DOI: 10.1152/ajpendo.00446.2006
|View full text |Cite
|
Sign up to set email alerts
|

Long-chain n-3 polyunsaturated fatty acids dissociate phosphorylation of Akt from phosphatidylinositol 3′-kinase activity in rats

Abstract: Le Foll C, Corporeau C, Le Guen V, Gouygou J-P, Bergé J-P, Delarue J. Long-chain n-3 polyunsaturated fatty acids dissociate phosphorylation of Akt from phosphatidylinositol 3Ј-kinase activity in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 44 publications
5
26
0
1
Order By: Relevance
“…In accordance with previous studies (1,25) we found that the preserved insulin sensitivity in cardiomyocytes coincubated with EPA or DHA during HI conditions was not associated with changes in the total cellular content of GLUT4. Because of experimental limitations, we were not able to measure GLUT4 translocation (surface GLUT4).…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with previous studies (1,25) we found that the preserved insulin sensitivity in cardiomyocytes coincubated with EPA or DHA during HI conditions was not associated with changes in the total cellular content of GLUT4. Because of experimental limitations, we were not able to measure GLUT4 translocation (surface GLUT4).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, decreased phosphorylation of AKT and increased GSK-3β were found in the diabetic rats, which may contribute to impact the insulin signaling in DRG neurons. The effect of n-3 PUFA on the activity of PI3K/AKT was tissue-specific, for example, a potent inhibitory effect in the liver and muscle contrasting with a potent stimulatory effect in adipose tissue in normo-insulin-sensitive rats [45,46]. Couplan et al [47] suggested that the effect of n-3 PUFA on PI3K activity was independent of other molecules in the PI3K/AKT pathway, such as IRS-1 or IRS-2, which might partially explain the effect of FO on AKT phosphorylation without changing IR or IRS-1 in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary supplementation with polyunsaturated fatty acids is thought to improve NAFLD by preventing lipid peroxidation, positively influencing peripheral insulin resistance, activating PPAR␣, and suppressing lipogenic transcription factor SREBP-1 (Keller et al, 1993;Sekiya et al, 2003;Gutiérrez et al, 2007;Le Foll et al, 2007). Studies in mice suggested that microcirculatory failure in macrosteatotic livers might be corrected by dietary supplementation of PUFAs through correction of reduced levels of n-3 and n-6 PUFAs in livers of patients with NAFLD (El-Badry et al, 2007;Allard et al, 2008).…”
Section: Other Approachesmentioning
confidence: 99%
“…The value for the dietary supplementation of PUFAs in NAFLD has been questioned by findings in a murine model of steatohepatitis, in which n-3 PUFAs failed to prevent the development of steatohepatitis because of accumulation of hepatic lipoperoxides (Larter et al, 2008a). Such effect, however, may be encountered by Sekiya et al, 2003;Capanni et al, 2006;Le Foll et al, 2007;Allard et al, 2008;Machado et al, 2008 340 ANDERSON AND BORLAK combination with other antioxidative strategies, such as treatment with vitamin E. Data from clinical studies had indicated that dietary supplementation with vitamin E in patients with NASH is associated with significant effects on liver transaminase levels and histopathology of NASH, and it may improve serum TNF-␣ levels (Lavine, 2000;Hasegawa et al, 2001;Harrison et al, 2003a;Kugelmas et al, 2003;Sanyal et al, 2004;Dufour et al, 2006;Yakaryilmaz et al, 2007). A combination of vitamin E with phospholipids and silymarin, an extract of milk thistle seed (silybum marianum), resulted in an improvement of hepatic steatosis (as assessed by ultrasonographic scores) and hyperinsulinemia, lowered liver transaminase levels and other indices of liver fibrosis as well as plasma levels of TGF-␤ and TNF-␣ in patients with NAFLD (Loguercio et al, 2007).…”
Section: Other Approachesmentioning
confidence: 99%